Surgeon's brooding Brazilian rival - DaRosa, Luana (Harlequin medical romance, 2024)
Everything else took a back seat as Sofia fought to become a trauma surgeon. She’s never met anyone who’s as dedicated and meticulous as her. Until world-renowned Dr. Carlos Cabrera arrives. But while her rival’s arrogance is exasperating, he makes her pulse race exponentially… The single thing Sofia and brooding Carlos agree on? The passion that sparked in the operating room can only end in the Brazilian’s bedroom!